PEMANFAATAN SATUA I CICING LAN I KAMBING MELALUI METODE BERMAIN PERAN SEBAGAI UPAYA MENINGKATKAN KARAKTER SISWA KELAS IV SD No. 2 MENGWI - I Wayan Sujana; Frederica Larashati; Ni Made Ailing Windiana Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the low level of students’ character development, particularly in terms of honesty and responsibility, in elementary school learning processes. In addition, less varied teaching methods make students less active and hinder their understanding of character values in a concrete way. This study aims to analyze the use of the Balinese folktale I Cicing lan I Kambing through role-playing methods as an effort to improve the character of fourth-grade elementary school students. The research employs a descriptive qualitative approach with 12 fourth-grade students as the subjects. Data were collected through observation and a learning style questionnaire. The results show that students’ learning styles are predominantly kinesthetic (58.33%), indicating that activity-based learning such as role play is more suitable. The use of folktales through role-playing methods helps students better understand values such as honesty, responsibility, and self-control. Therefore, this approach contributes as an effective alternative for culture-based learning in strengthening character education in elementary schools.